Altruistic Behavior in Generation Z: Systematic Literature Review - Kaltsum, Salma Yulya; Izzati, Indah Dwi Cahya; Fitriani, Annisa (Psikoborneo: Jurnal Ilmiah Psikologi, 2026)
The evolution of digital technology has changed the way Generation Z communicates and shows kindness, leading to new kinds of selflessness in the online world. On the other hand, the frequent use of social media raises concerns about how stable empathy and social awareness are within this age group. This research aims to explore the traits of helpful actions in Generation Z and the internal and external elements that shape these actions. A systematic literature review methodology was used in accordance with PRISMA standards. Literature searches were performed across databases such as Scopus, Google Scholar, Garuda, ResearchGate, SpringerOpen, and Semantic Scholar for articles published between 2021 and 2025. Forty suitable articles were assessed through narrative synthesis, and their quality was checked with the SANRA tool. The findings reveal that the altruism of Generation Z is complex and dependent on the context, heavily influenced by online activities like virtual contributions, social assistance, and sharing information. Internal factors like empathy, religious beliefs, and emotional intelligence were found to be the most significant, while external influences included social media, cultural expectations, the digital landscape, and crisis situations. These results illustrate that the altruistic actions of Generation Z stem from the interplay between psychological aspects and a changing social surroundings.Perkembangan teknologi digital telah mengubah cara Generasi Z berinteraksi dan mengekspresikan perilaku menolong, sehingga memunculkan bentuk-bentuk altruisme baru di ruang digital. Di sisi lain, tingginya penggunaan media sosial juga menimbulkan pertanyaan mengenai konsistensi nilai empati dan kepedulian sosial pada generasi ini. Penelitian ini bertujuan mengidentifikasi karakteristik perilaku altruisme pada Generasi Z serta faktor-faktor internal dan eksternal yang memengaruhinya. Penelitian menggunakan metode Systematic Literature Review (SLR) dengan pedoman PRISMA. Pencarian literatur dilakukan pada database Scopus, Google Scholar, Garuda, ResearchGate, SpringerOpen, dan Semantic Scholar terhadap artikel yang diterbitkan pada periode 2021–2025. Sebanyak 40 artikel yang memenuhi kriteria inklusi dianalisis menggunakan sintesis naratif dan dievaluasi kualitasnya dengan instrumen SANRA. Hasil penelitian menunjukkan bahwa altruisme Generasi Z bersifat multidimensional, kontekstual, dan didominasi oleh aktivitas digital seperti donasi daring, dukungan sosial, serta berbagi informasi. Empati, religiositas, dan kecerdasan emosional merupakan faktor internal yang paling berpengaruh, sedangkan media sosial, norma sosial, budaya digital, dan kondisi krisis menjadi faktor eksternal utama. Temuan ini menunjukkan bahwa perilaku altruisme Generasi Z merupakan hasil interaksi antara faktor psikologis dan lingkungan sosial yang terus berkembang.